Cost and returns structure in commercial broiler farming in Andaman and Nicobar islands - Kumar, B Ganesh; Rai, R B (The Indian Journal of Animal Sciences, 2011)
The study was taken up to workout the cost and returns structure in commercial broiler farming in Andaman and Nicobar Islands. About 60 broiler farms ofhaving different sizes, viz. small Â« 300 birds), medium (301-900 birds) and large (> 901 birds) were selected in some villages of south Andaman Island by random sampling. Data on inputs such as chick, feed, labour, medicine and vaccine, electricity and other miscellaneous items alongwith cost incurred on them and outputs such as live broilers of marketable age and gunny bags alongwith returns obtained from them in broiler farming, investment required for construction of poultry sheds and purchase of equipment such as feeder, waterer, buckets, metals and plastic utensils, weighing balance etc. were collected. The total fixed cost was estimated to be Rs 1133,4376 and 3930 for small, medium and large farms respectively. Overall, the total fixed cost was 5.49, 7.38 and 4.15 %ofthe total cost respectively. The total variable cost ofthe small, medium and large farms were estimated to be Rs 19520, Rs 54885 and Rs 90682, accounting for 95.51,92.62 and 95.85 % respectively. Among the various components ofvariable cost, the feed cost and chick cost were the main items ofexpenditure. Almost two-third of the total cost was incurred on feed only in all the categories ofthe farms. The next in order were labour cost, medicine and vaccine expenses, electricity charges and miscellaneous expenditure. The total cost ofproducing an average batch size of300, 900 and 1500 birds was worked out to be Rs 20653, 59261 and 94612 respectively. The cost ofproduction of broilers was worked out to be Rs 68.84,65.85 and 63.07 for small, medium and large farms respectively. Total return form the three different sizes ofbroiler farms was Rs 23 160, 69480 and 115800. Net return per batch was estimated to the Rs 2507,10219 and 21188 for small, medium and large farms respectively. The net return per bird was Rs 8.36, 11.35 and -14.13 and the B:C ratio was 1: 1.12, 1: 1.17 and 1: 1.22, respectively, for the 3 categories of farms. The optimum size of broiler unit was estimated to be 166,505 and 2436 for small, medium and large farms respectively. It was found that broiler farming was a profitable venture in Andaman and Nicobar islands and it proved to be the main source of income to a sizeable number of farmers here. Â